TOKSISITAS SUBAKUT EKSTRAK BIJI PEPAYA (Carica papaya L.) TERHADAP AKTIVITAS ENZIM Serum Glutamic Oxaloasetic Transminase (SGOT) MENCIT (Mus musculus) SECARA IN VIVO - Safwan Safwan; Abdul Rahman Wahid; Ali Ridho Husein; Ni_Nyoman Mira Mentari (Universitas Wahid Hasyim Semarang, 2017)
ABSTRACT The aim of this study was to investigate the subchronic toxicity of extract of papaya seed (Carica papaya L.) on rat by evaluate Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic Oxaloasetic Transaminase (SGOT) activity. Twenty (20) white male miceswere randomly grouped into four groups (one control and three treatment groups). Group 1 received 1% of CMCNa. Group 2, 3, and 4 received extract of papaya seed at a dose of 50 mg/kg body weight, 500 mg/kg body weight, and 5000 mg/kg body weight. After 28 days treatment, blood samples were collected from jugular vein near the eye to evaluate SGPT and SGOT level in serum. Data were analyzed using ANOVA (at 95% confidence). It is observed that extract of papaya seed at a dose 50 mg/kg body weight, 500 mg/ kg body weight, and 5000 mg/kg body weight have no effect to increase SGPT and SGOT activity. Key Word : Papaya Seed,Subacute, Toxicity, SGPT, SGOT